2013
DOI: 10.1590/s1413-80502013000400001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of subsidized health insurance on the poor in Colombia: evaluating the case of Medellín

Abstract: This paper uses count and binary data models with an endogenous dummy variable to evaluate the effect of the subsidized health care program in Medellin (Colombia). The subsidized program, which primarily covers poor people, is found to have a significant impact on the use of preventive medical care and hospitalization that might have a negative impact on the financial statements of the program. Specifically, econometric estimations of health care utilization indicate that there is both selection and moral haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(23 reference statements)
0
1
0
Order By: Relevance
“… 4 There has been reported that people in the subsidized insurance are less likely to use preventive services and claim medicines. 27 , 35 , 36 These data may reflect that access barriers to medicines and other interventions in the subsidized insurance could account for the lower blood pressure control rates in this population.…”
Section: Discussionmentioning
confidence: 97%
“… 4 There has been reported that people in the subsidized insurance are less likely to use preventive services and claim medicines. 27 , 35 , 36 These data may reflect that access barriers to medicines and other interventions in the subsidized insurance could account for the lower blood pressure control rates in this population.…”
Section: Discussionmentioning
confidence: 97%